Pengaruh Penggunaan Comic Life Terhadap Kemampuan Scientific Explanation Dan Hasil Belajar IPA - Septian Pawulan C. Lestari; Supeno Supeno; Iwan Wicaksono (Musamus Journal of Science Education, 2021)
This research uses a quantitative approach with a quasi-experimental research type, which aims to determine the effect of the use of comics on the ability of scientific explanation and science learning outcomes. The sample in this study were students of class VIII junior high school using 2 classes as the control class and the experimental class where the class was not randomly selected. Each class between the experimental class and the control class corresponds to 35 people. This study used a quasi experimental design. The research design used Post-test Only Control Design. The data learning technique is in the form of a post-test which is done at the end of the lesson. Analysis method The assessment of students' learning abilities and outcomes uses statistical tests in the form of the Independent Sample T-test with the help of SPSS. The results showed the average value of the scientific explanation ability of the experimental class was 92.00 while the control class was 51.20, and the experimental class learning outcomes average was 88.00, while the control class was 78.43. The influence of the influence of the use of comic life as a science learning media on the ability of scientific explanation and learning outcomes in junior high school students has a significant effect